AN INDUSTRIAL APPLICATION OF IMPROVED PARTICLE SWARM OPTIMIZATION: AVAILABILITY ASSESSMENT OF ELECTROSTATIC PRECIPITATOR - Bolourchi, Pouya; Gholami, Mohammadreza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The Electrostatic Precipitator (ESP) is common equipment used in thermal power plants and industrial mining plants such as steel, copper, and cement. ESP is installed to capture the dust in the exhaust gas of boilers or furnaces. The availability of ESP is vital for plants since any interruption in this device causes serious process problems and environmental pollution. As a result, the availability of ESP is crucial, and a comprehensive study in this area must be performed for maintenance activities. This paper presents a novel method for assessing complex equipment availability, such as ESP, based on improved dynamic particle swarm optimization (IDPSO). To evaluate the availability of ESP, all related systems, sub-systems, and all components of ESP must be considered. Availability assessment of ESP, consisting of many series-parallel sections and components, can be challenging and time-consuming. An IDPSO is used to search for the most probable states among numerous possible states. In addition, IDPSO overcomes shortcomings of standard PSO, such as falling into local optimums. The proposed method is applied to the actual data of an ESP installed at a copper factory. The results show the proposed method achieved an accuracy of 99.54 % in availability assessment.